Pollutant dispersion modelling (Dust, CO, NOx, and SOx) from palm oil mill stack (Case Study of PT. Mustika Agung Sawit Sejahtera) - Hermantika Sari, Nadya Hermantika x; Tarumun, Suardi; ', Saryono (Universitas Riau, 2014)
Pollutant dispersion modeling study of a stack is one of the efforts in addressing the problems thatemissions of the palm oil industry can match the capacity of the environment, so it will not impact on the envi ronment and society. Screeen view SCREEN3 software, based of Gaussian dispersion method for dust, CO, NOx, and SOx pollutant, was used for pollutant dispersiion modeling. The input parameters in the simulation were the rate of emission of pollutants emitted from the stack, the air velocity around the source of emissions, atmospheric stability factor, and the topography of the site. While the expected output was a visualization of dis tribution of pollutants concentration in the form of 2-dimensional plane-shaped contour that came with concen tration values of the distance from the source of emission. Modeling in this study was conducted with several scenarios that the average meteorological conditions at the time of measurement and the worst conditions. The results showed that the dominant wind direction was to the south with an average speed of 5.87 m/s. The result ing emission rate was 36.4 g/s. As for the pollutants, CO was 13.84 g/ s, SOx was 0.213 g/s and NOx 24.49 g/ s. Emission maximum distance was 1340 m from the stack with dust concentration at 133.9 ug/m3 The concentra tions of CO, NOx, and SOx were 50.90 ug/m3 90.06 ug/m3; 0.7833 ug/m3 respectively.Keywords: environment, pollutant dispersion modeling, stack, palm oil mill, Gaussian dispersion method, Screen viewScreen3